Reporting a Case of Solid Pseudopapillary Neoplasm of the Pancreas in a 44-Year-Old Woman with Parallel Analysis of Literature - Sargun Singh; Qing Zhao; Teviah E. Sachs; Kevan Hartshorn (Case Reports in Oncological Medicine)
We present a distinctive case of solid pseudopapillary neoplasm as seen in a 44-year-old woman who presented with an abdominal mass but unremarkable labs with no elevation in any of the tumor markers. Her symptomatology ranged from typical symptoms suggestive of malignancy such as weight loss, lethargy, and anorexia to complaints like abdominal pain and jaundice. Prior to presenting at our center, she was given no hope or much in terms of treatment options. She was found to have a substantial mass over the body and tail of pancreas with characteristic and typical gross as well as histological features. Subsequently, she underwent a successful surgery and has found herself in remission since.